Work Related Quality of Life of Female Garment Workers (TAJ: Journal of Teachers Association, 2019)
Background: Readymade Garment (RMG) was the key source of earning foreign currencies and had been playing a vital role in creating employment opportunity for the rural marginal people since long. This study explored the work related quality of life of female garment workers.Methods: This cross sectional study was conducted during July 2016 to June 2017 and data were collected from 400 female garment workers through face to face interview by using a semi-structured questionnaire. Results: The average age of the garment workers was 23.09 years. Most (86%) of the workers had some level of education and only 14% had no formal education. The workers’ minimum and maximum monthly income was BDT 8500 and BDT 33500 respectively. Most of them agreed that they had good infrastructure, sanitation and safety facilities in the work place. All the workers (100%) were satisfied with job facilities and majority (72%) had a clear understanding about goals and aims to do their job at workplace. The workers also had positive impression about the issues related to job satisfaction and working condition. The study also discussed about the sexual issues. 6%, 7% and 9% of the female workers agreed respectively that they were sexually abused in the job, by the co-workers and by the supervisors. Most of the workers agreed to the statement that this job helped them to maintain a good quality of life and they were more respected in the family and society. Educational status, monthly income, infrastructure, sanitation and health safety facilities were statistically significant with the work related quality of life (p =